Low-Scattering-Cross Section Thinned Phased Array Antenna Based on Active Cancellation Technique - Li, Peng-Fa; Qu, Shi-Wei; Yang, Shiwen; Hu, Jun (IEEE transactions on antennas and propagation, 2022)
In this article, a novel approach to simultaneously reduce the scattering cross section (SCS) and lower sidelobe level (SLL) as well as the cost of a phased array is proposed, which is a combination of active cancellation and array thinning techniques. Two 10 ×\,\,10 planar microstrip phased arrays are designed to validate the proposed concept, including a full array and a thinned array with 20 passive elements. In the thinned array, the passive elements are made use of and terminated at an optimized position with short-circuited loads to generate scattering fields with the required magnitude and phase for cancellation of the scattering fields from the active elements. Furthermore, the positions of the passive elements are optimized by a multiple dimensional discrete particle swarm optimization (MDDPSO) algorithm to achieve a low SLL. It is theoretically predicted that the thinned array features a low SLL below −18 dB in a scan range of ±45°, and SCS reductions of 21 and 9.1 dB in 7.3-10.1 GHz compared to an equal-sized metallic plate and a full array, respectively, which are further verified in simulations and measurements. It is also remarkable that the array cost is reduced due to array thinning, at the cost of an approximately 1 dB gain drop.